2018
DOI: 10.21873/anticanres.12896
|View full text |Cite
|
Sign up to set email alerts
|

Panobinostat and Nelfinavir Inhibit Renal Cancer Growth by Inducing Endoplasmic Reticulum Stress

Abstract: Background/Aim: There is no curative treatment for patients with advanced renal cancer. We believed that the combination of the histone deacetylase inhibitor panobinostat and the human immunodeficiency virus protease inhibitor nelfinavir would kill renal cancer cells by inducing endoplasmic reticulum (ER) stress. Materials and Methods: Using renal cancer cells , the ability of this combination to induce ER stress and its mechanism of action were investigated. Results: The combination of drugs induced apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
(45 reference statements)
6
15
0
Order By: Relevance
“…In the present study, inhibition of ER stress by cycloheximide markedly impaired the combination's ability to cause histone acetylation and induce apoptosis, suggesting that the ER stress induction played a pivotal role in the combination's action. This ER stress-histone acetylation sequence is also consistent with our previous results that there is a crosstalk between histone acetylation and ER stress induction [29,30,73,74,80]. The decreased expression of HDACs is thought to be a consequence of the ER stress induction according to the previous studies [29,30,73,74,80].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, inhibition of ER stress by cycloheximide markedly impaired the combination's ability to cause histone acetylation and induce apoptosis, suggesting that the ER stress induction played a pivotal role in the combination's action. This ER stress-histone acetylation sequence is also consistent with our previous results that there is a crosstalk between histone acetylation and ER stress induction [29,30,73,74,80]. The decreased expression of HDACs is thought to be a consequence of the ER stress induction according to the previous studies [29,30,73,74,80].…”
Section: Discussionsupporting
confidence: 92%
“…This ER stress-histone acetylation sequence is also consistent with our previous results that there is a crosstalk between histone acetylation and ER stress induction [29,30,73,74,80]. The decreased expression of HDACs is thought to be a consequence of the ER stress induction according to the previous studies [29,30,73,74,80]. This HDAC suppression might further enhance the histone acetylation and even the ER stress because HDAC suppression abrogates molecular chaperone function, causing the accumulation of unfolded proteins [70][71][72].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another important mechanism of AMPK activation is regulation of the AMPK-activating calcium/calmodulin-dependent kinase kinase (CaMKK)-beta by ER stress (12,29,30). Furthermore, our previous studies revealed that ER stress induction is closely associated with AMPK activation (31,32). Thus, ER stress is closely related to regulation of AMPK.…”
Section: Discussionmentioning
confidence: 99%